Quality Attributes of Immature Fruit of Different Mango Varieties - Mujahid Hussain Leghari,; Saghir Ahmed Sheikh,; Noor-un-nisa Memon,; Aijaz Hussain Soomro ,; Aijaz A. Khooharo, (Journal of Basic & Applied Sciences, 2013)
The study was carried out to evaluate quality attributes of immature fruits of four commercially grown varieties of mango namely Sindhri, Chaunsa, Langra and Desi. The immature mango fruits were collected from basin of mango tree in the end of April followed by washing, surface drying and extraction of fruit pulp. The extracted fruit pulp was assessed for pH, TSS, moisture and ash percentage, acidity, vitamin C, fat, protein and sugars. Besides, minerals including sodium, calcium, potassium, magnesium, zinc, iron, copper, chromium, and manganese were also determined. On the basis of varietal comparison Sindhri had more moisture (88.60%), ash and fat (0.60%) each, total sugars (6.99%) and reducing sugars (2.78%) as compared to rest of the varieties. However TSS (9.35%), protein (0.71%), and non reducing sugars (4.86%) were recorded the highest in Langra variety. Only the Chaunsa variety had maximum pH of 3.01 and vitamin-C (27.16 mg 100g-1). Regarding mineral elements, Desi was found potential in terms of sodium (453.93 mg kg-1), calcium (403.79 mg kg-1), Zinc (3.47 mg kg-1) and iron (5.95 mg kg-1). The zinc and iron was at par with the results obtained from Langra. However, potassium (904.58 mg kg-1) and copper (2.58 mg kg-1) were observed the highest in Langra, magnesium (78.09 mg kg-1) in Chaunsa and manganese (2.43 mg kg-1) in Sindhri.